Financial Literacy’s Moderating Role in Savings and MSME Sustainability: Evidence from Central Java, Indonesia - Efriyani sumastuti; C. Tri Widiastuti; Rizka Ariyanti; Ali Imron (Quantitative Economics and Management Studies, 2025)
The objective of This investigation is to investigate the influence of financial inclusion and financial literacy on the sustainability of businesses, with business savings serving as a mediating factor and financial literacy acting as a moderator. The study involved 150 culinary MSMEs in Central Java and utilized a quantitative method with the SmartPLS 3.0 analytical tool. The findings suggest that financial literacy and financial inclusion significant direct influences on business sustainability. Additionally, Financial literacy significantly influences business savings, highlighting its important role in shaping the financial behaviors of MSMEs. On the other hand, business savings do not show a statistically significant direct impact on business sustainability, and their mediating role receives only partial support. The moderating effect of financial literacy on the connection between business savings and business sustainability is significant but in a negative direction. These results suggest that while financial literacy is generally advantageous, it can change the role of savings if not integrated with effective financial planning. This research provides a theoretical contribution to the comprehension of financial behavior models in MSMEs and supports the achievement of SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure) through inclusive financial empowerment.